Pengembangan Tanaman Kakao di Desa Bontula, Kecamatan Asparaga, Kabupaten Gorontalo - Ikraeni Safitri; Mustamin Ibrahim (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Cocoa (Theobroma cacao L.) is included in the Sterculiaceae family and is a plantation crop originating from South America and is currently widely planted in the tropics. Cocoa is used in parts of the fruit such as fruit skin, pulp and seeds. . Cocoa is a strategic Indonesian export commodity that generates foreign exchange, but it is undeniable that its industry is still hampered so that it imports cocoa in finished products. Activities in the development of cocoa carried out in Bontula Village involve monoculture farming communities. The development of cocoa plants in Bontula Village is a plant that is the result of vegetative propagation, namely by grafting techniques. The activity begins with education in the introduction of cocoa types and then planting is carried out on community plantation land which is a demonstration plot. This activity shows good results in terms of community awareness in planting cocoa and maintaining plants so that it has a high percentage of the percentage of cocoa plant life.